Potential of Silybum marianum Aqueous Extract to Inhibit Rhizoctonia solani Growth and Pathogenesis - Al-Thabhawi, Saleh H; Al-Haidary, Firas H; Khalaf, Hussein A; Kadhim, Jamal H (Department of Agronomy and Horticulture, IPB University, 2026)
The present study evaluated the effects of a cold aqueous extract of milk thistle (Silybum marianum) on the growth of the soil-borne pathogen Rhizoctonia solani and on wheat seed germination and seedling development. In vitro assays demonstrated that the extract significantly inhibited fungal growth, with concentrations up to 7.5% completely preventing proliferation. Pot experiments further revealed that soil treated with both R. solani biomass and its culture medium, particularly in the presence of milk thistle extract, resulted in a drastic reduction in wheat seed germination to 30% and complete seedling mortality within 10 days. Notably, when fungal biomass and its medium were treated with increasing concentrations of milk thistle extract (2.5%–10%), wheat seed germination rates improved markedly, ranging from 83% to 93%. In comparison, seedling death decreased from 16% to 10%. Furthermore, seedlings grown under these conditions exhibited significant increases in shoot and root length, as well as overall biomass, compared with controls grown on potato dextrose agar (PDA) alone. These results suggest that milk thistle extract may serve as an effective pre-planting seed treatment, enhancing wheat germination and seedling vigor while reducing susceptibility to Rhizoctonia solani during early developmental stages.